ANALISIS EFISIENSI BIAYA DISTRIBUSI PRODUK UNILEVER TAHUN 2018 - 2020 PADA PT. ARINA MULTIKARYA SURABAYA - Riyanah; Indriana Nikita, Nia (Universitas Pawyatan Daha, 2022)
The purpose of this study is to determine the cost efficiency of Unilever's product distribution. The data sources that the authors use are primary data and secondary data. Data analysis used in this research is descriptive analysis and efficiency analysis. Whereas Unilever product distribution costs for 2018-2020 PT. Arina Multikarya is already efficient, with the distribution of products in cities that have a high efficiency value, namely in 2018 and 2019 it was 0.04% while in 2020 it was 0.03% with an average level of efficiency of 0.03% and an average return on investment of 27.94%, compared to out-of-town distribution using land transportation and out-of-town distribution using land and sea transportation, which is an average level of efficiency of 0.05% and an average return of investment of 19.24% for out-of-town distribution using land transportation and 0.04% and an average return of investment of 22.61% for out-of-town distribution using land and sea transportation.